Persistent Symptoms and Health Needs of Women and Men With Non-Obstructed Coronary Arteries in the Years Following Coronary Angiography - Groepenhoff, Floor; Eikendal, Anouk L. M.; Rittersma, Z. H. Saskia; Gijsberts, Crystel M.; Asselbergs, Folkert W.; Hoefer, Imo E.; Pasterkamp, Gerard; Rutten, Frans H.; Onland-Moret, N. Charlotte; Den Ruijter, Hester M. (Frontiers in Cardiovascular Medicine, 2021)
Background The prognosis of women and men with persistent anginal complaints and non-obstructed coronary arteries is impaired as compared with asymptomatic women and men. The increased healthcare burden in the hospital due to repeated coronary angiography in these women and men has been documented, yet little is known about the percentage of women and men who remain symptomatic and under care of the general practitioner in the years following a coronary angiographic outcome of non-obstructed coronary arteries. Methods From the Utrecht Coronary Biobank study, including individuals who underwent a coronary angiography from 2011 to 2015 (N = 2,546, 27% women), we selected women and men with non-obstructed coronary arteries (N = 687, 39% women). This population was linked to the Julius General Practitioners Network (JGPN); a database with routine care data of general practitioners. For every individual with non-obstructed coronary arteries, we selected an asymptomatic non-referred age-, sex- and general practitioner-matched individual from the JGPN. We compared the healthcare consumption of men and women with non-obstructed coronary arteries to these matched individuals. The McNemar’s test was used for pairwise comparison, and sex differences were assessed using stratified analyses. Results The prevalence of non-obstructed coronary arteries was higher in women as compared with men (39% vs. 23%). During a median follow-up of 7 years [IQR 6.4-8.0], 89% of the individuals with non-obstructed coronary arteries (91% women and 87% men) visited their general practitioner for one or more cardiovascular consultations. This was compared to 34% of the matched individuals (89% vs. 34%, p<0.001). The consultations were most often for angina (equivalents) (57% vs. 11%, p<0.001) and heart failure (10% vs. 2%, p=0.015). In addition, they more often consulted the general practitioner for psychosocial complaints (31% vs. 15%, p = 0.005). Findings were similar for women and men. Conclusions A coronary angiographic outcome of non-obstructed coronary arteries is more common in women than in men. In the years following the coronary angiography, the majority of the population remains symptomatic. Both women and men with non-obstructed coronary arteries had higher health needs for angina, heart failure and psychosocial complaints than matched asymptomatic individuals.